Efficacy and safety of a novel herbal solution for the treatment of androgenetic alopecia and comparison with 5% minoxidil: A double‐blind, randomized controlled trial study. Issue 6 (5th November 2020) - Masoud, Farid; Alamdari, Hamideh Azimi; Asnaashari, Solmaz; Shokri, Javad; Javadzadeh, Yousef
Abstract: FDA‐approved drugs for the most common type of hair loss, androgenetic alopecia (AGA), present many side effects and disadvantages. However, herbal compounds are characterized by patient compliance, fewer side effects, and several mechanisms of action. The present study set to evaluate the effectiveness and safety of the topical herbal solution and to compare it with 5% minoxidil in men with AGA. A randomized, double‐blind controlled trial was conducted from 28 November 2018 to 2 September 2019, in Sina Hospital, Tabriz, Iran. 24 healthy males (mean [SD] age 33.04 [5.81]) with mild to moderate AGA were selected from 44 volunteer participants. Participants were randomly assigned (1:1) into two groups. They received 1 ml of topical solutions at morning and evening intervals for 9 months. Primary outcomes consisted of measured hair diameters at baseline and repeated at weeks 12, 24, and 36. Furthermore, hair density was measured at baseline and week 36. The MTS + THS group was significantly superior to the MTS group after 36 weeks of therapy in the hair diameter improvement. At week 36, the mean hair diameter of the MTS + THS group significantly increased compared to the MTS group ( P = .001). Hair density increased in both groups; however, only in the MTS + THS group, it was significant ( P < .05). The findings established that the topical herbal solution has significant influence on patients with AGA and improvement of their quality of life. This solution can be considered a significant step towards the prevention and treatment of AGA. clinicaltrials.gov Identifier: NCT03753113.